Development of Higher Education Curriculum Based On Independent Learning-Independent Campus (MBKM) Islamic Education Study Faculty of Tarbiyah and Teaching Sciences UIN Sunan Kalijaga Yogyakarta - Mega Melani Ramadani; Muh. Wasith Achadi (Universitas Muhammadiyah Enrekang, 2024)
This research aims to analyze the efforts of the Ministry of Education and Culture to improve the quality and relevance of graduates through the Independent Learning-Free Campus (MBKM) policy. The implementation of MBKM requires special attention to the development of the Islamic Religious Education Study Program (PAI) curriculum, including adjustments to Graduate Learning Outcomes (CPL), vision and mission, graduate profiles, courses, Body of Knowledge (BoK), and study language. The PAI curriculum development process also involves mapping courses according to categories, determining study materials, and descriptions to facilitate curriculum preparation. With an integrative approach, curriculum development at MBKM aims to achieve graduate competency standards from spiritual aspects and moral nobility. This document also highlights the importance of involving expert lecturers from various study programs in curriculum formulation, and emphasizes the need to determine courses to support the MBKM curriculum. Through a good curriculum development process, it is hoped that the PAI study program can produce graduates who are not only good at theory, but also able to excel in various other aspects.